2015
DOI: 10.14800/ccm.1023
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Modulation of Androgen Receptor Signaling: Implications for Prostate Cancer

Abstract: Androgens and androgen receptors play essential roles in the development and progression of prostate cancer, a disease that claims roughly 28,000 lives annually. In addition to androgen biding, androgen receptor activity can be regulated via several post-translational modifications such as ubiquitination, acetylation, phosphorylation, methylation & SUMO-ylation. Off these modifications, phosphorylation has been the most extensively studied. Modification by phosphorylation can alter androgen receptor localizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 72 publications
0
14
0
1
Order By: Relevance
“…Castration levels of hormone modulate AR activity through its phosphorylation at multiple sites [ 4 , 31 ]. As the analysis of each phosphorylated residue can give discordant results depending on cellular context or tumor microenvironment, we evaluated the total AR phosphorylation status using the Phos-tag SDS-PAGE technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Castration levels of hormone modulate AR activity through its phosphorylation at multiple sites [ 4 , 31 ]. As the analysis of each phosphorylated residue can give discordant results depending on cellular context or tumor microenvironment, we evaluated the total AR phosphorylation status using the Phos-tag SDS-PAGE technique.…”
Section: Resultsmentioning
confidence: 99%
“…Since the AR transcriptional activity is positively regulated by its phosphorylation status [ 31 ], we determined AR activity by transfecting LNCaP, PDB and MDB cells with a plasmid expressing the luciferase reporter gene driven by a promoter containing an androgen response element (ARE). In the presence of 10 nM DHT, LNCaP cells increased AR activity approximately 11-fold, while PDB and MDB exhibited activity levels reduced by 61 and 80%, respectively, compared to LNCaP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, LMTK2 gene polymorphisms associated with decreased LMTK2 mRNA and protein levels were found in prostate cancer tissues (10,19,28). Furthermore, studies demonstrated that LMTK2 interacts with the androgen receptor (AR) and inhibits its activity (10,12). The role of LMTK2 in other pathological processes, such as the lung, gastric, and colorectal cancer as well as infertility has not been well established.…”
Section: Discussionmentioning
confidence: 99%
“…Lemur Tyrosine Kinase 2 interacts with AR and inhibits its transcriptional activity (Shah and Bradbury, 2015a,b). AR promotes cell growth and plays an important role in prostate development (Chang et al, 1988; Mangelsdorf et al, 1995).…”
Section: The Lmtk2 Interactomementioning
confidence: 99%
“…The role of LMTK2 in prostate cancer is well established (Eeles et al, 2008; Guy et al, 2009; Waters et al, 2009; Harries et al, 2010; Wang et al, 2013; Shui et al, 2014; Shah and Bradbury, 2015a,b; Hao et al, 2016; Jiang et al, 2016). The lmtk2 gene was identified as one of seven loci associated with prostate cancer in a genome-wide association study (GWAS) using blood DNA from 1854 individuals with prostate cancer detected before 60 years of age or with a family history of the disease (Eeles et al, 2008; Guy et al, 2009).…”
Section: Role Of Lmtk2 In Human Disease: Potential Biomarker and Thermentioning
confidence: 99%